Developing a Strategic Perspective for Managerial Accounting By Using Value Chain Analysis (Al-Mansour Journal, 2022)
The development of business organization's activities, especially in strategic aspects makes it necessary for accounting to keep pace with it. This is the focal point of the present paper which aims at defining and analyzing the strategic perspective which can be adopted by managerial accounting particularly, in the execution of the strategies of operational activities in the light of various factors and variables that do influence the environment of business organization. In addition to that, the paper aims at explaining the integrated relationship that connect a number of contemporary concepts and approaches which form the intellectual base of managerial accounting. These concepts and approaches can be of practical use in the field of analyzing activities of Iraqi business organizations strategically. Moreover, the paper presents a number of analyses and explanations which support the view that the value chain provides a distinctive methodology that is of great value in the field of cost management according to the strategic perspective.The paper also defines additional conditions which can be considered as prerequisites for using the value chain analysis. These conditions are related to the necessity to provide a number of social and cultural factors that are of vital importance for preparing the proper bases to carry out the value chain. Finally, other technical and economical factors should be available too.